Skill-based Medical English Teaching in a Corporate Environment - Arani, Jafar Asgari (International Journal of Advanced Corporate Learning (iJAC), 2015)
Background: Medical English has been enjoying a good deal of popularity among doctors and medical students having an extraordinary effect on their competencies .This article proposes the use of a competency-based approach in a Blended-Learning English for Medical Purposes (EMP) course design for the students of medicine. The objectives of the study were to investigate the medical English needs of the students of medicine, to develop a Blended-Learning competency-based EMP course module for the students of medicine, and to examine the opinions of students toward the course module.Method& Materials: The study was a descriptive and experimental research. The course was taught using Drupal Platform and Web 2.0 tools as supplement to traditional face-to-face classroom. EMP needs were analyzed by interviewing 45 key students and a questionnaire survey with 140 students of medicine. The qualitative data from the interview were analyzed by content analysis while the quantitative data from the questionnaire survey were analyzed using descriptive statistics (mean, percentage, and standard deviation). For course evaluation, the pretest and posttest score were analyzed by comparing the mean scores of the pretest and posttest using t-test. Findings: The Blended Learning course module was validated by the experts and piloted with a group of learners having the similar characteristics as the subjects in the main study. The results of t = -15.09 indicated that the participants in the study had higher scores in their posttest than in the pretest at a significant level (p< .05). The standard deviation of all criteria (SD <1) shows that the consistency of the students opinions responses did not vary much. Conclusion: Blended-Learning competency-based English course module can meet the needs of the students of medicine in terms of the EMP course which has conceptualized the content around the competencies needed for their studies.